2017
DOI: 10.1007/s00702-017-1699-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis between patients with probable Alzheimer’s disease, Parkinson’s disease dementia, or dementia with Lewy bodies and frontotemporal dementia, behavioral variant, using quantitative electroencephalographic features

Abstract: The objective of this work was to develop and evaluate a classifier for differentiating probable Alzheimer’s disease (AD) from Parkinson’s disease dementia (PDD) or dementia with Lewy bodies (DLB) and from frontotemporal dementia, behavioral variant (bvFTD) based on quantitative electroencephalography (QEEG). We compared 25 QEEG features in 61 dementia patients (20 patients with probable AD, 20 patients with PDD or probable DLB (DLBPD), and 21 patients with bvFTD). Support vector machine classifiers were train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 67 publications
2
78
1
Order By: Relevance
“…The first analysis showed significant positive correlations between MMSE scores (roughly reflecting global cognitive status) and LLC solutions in interhemispheric temporal and intrahemispheric diffuse alpha sources across all Nold, ADD, DLB, and PDD individuals as a whole group. However, even if statistically significant (p < 0.005), the correlation values were relatively low as variance explained (2) 0.92-0.78 for MCI vs. ADD individuals; and (3) 0.87-0.60 for the conversion from MCI to ADD status (Adler et al, 2003;Babiloni et al, 2015bBabiloni et al, , 2016bBennys et al, 2001;Blinowska et al, 2017;Brassen et al, 2004;Buscema et al, 2007;Claus et al, 1999;Engedal et al, 2015;Garn et al, 2017;Huang et al, 2000;Jelic et al, 2000;Knyazeva et al, 2010;Lehmann et al, 2007;Lizio et al, 2016;Missonnier et al, 2006;Nuwer, 1997).…”
Section: The Llc Solutions In Delta and Alpha Sources Classified Noldmentioning
confidence: 97%
See 1 more Smart Citation
“…The first analysis showed significant positive correlations between MMSE scores (roughly reflecting global cognitive status) and LLC solutions in interhemispheric temporal and intrahemispheric diffuse alpha sources across all Nold, ADD, DLB, and PDD individuals as a whole group. However, even if statistically significant (p < 0.005), the correlation values were relatively low as variance explained (2) 0.92-0.78 for MCI vs. ADD individuals; and (3) 0.87-0.60 for the conversion from MCI to ADD status (Adler et al, 2003;Babiloni et al, 2015bBabiloni et al, , 2016bBennys et al, 2001;Blinowska et al, 2017;Brassen et al, 2004;Buscema et al, 2007;Claus et al, 1999;Engedal et al, 2015;Garn et al, 2017;Huang et al, 2000;Jelic et al, 2000;Knyazeva et al, 2010;Lehmann et al, 2007;Lizio et al, 2016;Missonnier et al, 2006;Nuwer, 1997).…”
Section: The Llc Solutions In Delta and Alpha Sources Classified Noldmentioning
confidence: 97%
“…Another recent study in relatively small populations of ADD, PDD/DLB, and frontotemporal dementia patients used 25 discriminant scalp rsEEG power density and functional cortical connectivity (i.e. Granger causality) variables as an input to support vector machine, reaching a classification accuracy of 1.0 (Garn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another study in small populations of ADD, PDD/DLB, and frontotemporal dementia patients reached a classification accuracy of 1.0 using 25 discriminant scalp rsEEG power density and functional cortical connectivity (i.e. Granger causality) variables [375]. In another study, combining quantitative rsEEG variables (including those of functional cortical connectivity) with neuropsychological, clinical, neuroimaging, cerebrospinal fluid, and visual EEG data reached “only” a classification accuracy of 0.87 in the discrimination between ADD, PDD, and DLB persons [376].…”
Section: Contribution and Role Of Electroencephalography (Eeg)mentioning
confidence: 99%
“…Recently, neurophysiological activities have been reported to help in the differential diagnosis among dementias, including DLB . The latest DLB consensus criteria included EEG activities as a supportive biomarker, suggesting the clinical importance of neurophysiological activities in patients with DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, neurophysiological activities have been reported to help in the differential diagnosis among dementias, including DLB. 29,30 The latest DLB consensus criteria included EEG activities as a supportive biomarker, 31 suggesting the clinical importance of neurophysiological activities in patients with DLB. Our study revealed that DLB patients exhibit a significant reduction in the alpha ERS ratio in the posterior brain regions, including in the inferior temporal gyrus, the left parieto-occipital sulcus, and the right occipital pole, compared to AD patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%